Five new 2-(2-phenylethyl)chromone derivatives and three new sesquiterpenoids from the heartwood of Aquilaria sinensis, an aromatic medicine in China - Lu Zhang; Ping Yi; Hui Yan; Xiao-Nian Li; Meng-Yuan Xia; Jun Yang; Ji-Feng Luo; Yue-Qiu He; Yue-Hu Wang (Natural Products and Bioprospecting, 2022)
Abstract Five new 2-(2-phenylethyl)chromone derivatives, (5S,6R,7R,8S,7ʹR)-7ʹ-hydroxyagarotetrol (1), (5S,6R,7R,8S,7ʹS)-7ʹ-hydroxyagarotetrol (2), (6S,7S,8R)-2‑[2‑(4-methoxyphenyl)ethyl]‑6,7,8‑trihydroxy‑5,6,7,8‑tetrahydrochromone (3), (6S,7S,8R)-2‑(2-phenylethyl)‑6,7,8‑trihydroxy‑5,6,7,8‑tetrahydrochromone (4), (5S,6R,7S,8R)-2-(2-phenylethyl)-5,6,7-trihydroxy-5,6,7,8-tetrahydro-8-[2-(2-phenylethyl)-7-methoxychromonyl-6-oxy]chromone (5), three new sesquiterpenoids, (4S,5S,7S,8S,10S,13R)-7,8,13-trihydroxyrotunda-1,11-dien-3-one (6), (4S,5S,7S,8S,10S,13S)-7,8,13-trihydroxyrotunda-1,11-dien-3-one (7), and (4R,5S,7S,8S,10S,13S)-7,8,13-trihydroxyrotunda-1,11-dien-3-one (8), along with 14 known compounds were isolated from the resinous heartwood of Aquilaria sinensis (Thymelaeaceae). The chemical structures of these new compounds were elucidated by 1D and 2D NMR and MS data, single-crystal X-ray diffraction analysis, and electronic circular dichroism (ECD) calculations. The neuroprotective activities of these isolates were evaluated using an in vitro model of rat adrenal pheochromocytoma (PC12) cell injury induced by corticosterone. At concentrations from 5 to 40 µM, compounds 4 and 6, agarotetrol (9), and 6-hydroxy-2-(2-phenylethyl)chromone (17) showed significant protective activities against corticosterone-induced PC12 cell injury (P < 0.001). Graphical Abstract